2012
DOI: 10.1029/2011wr010829
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of sediment transport in step‐pool channels

Abstract: [1] In mountainous drainage networks, sediment mobilized on hillslopes must first pass through steep streams before reaching lower-gradient channels. The bed of steep channels is typically composed of large, relatively immobile boulders and finer, more mobile gravel. Most sediment transport equations overpredict sediment flux in steep streams by several orders of magnitude because they do not account for the stress borne by immobile grains and the limited availability of the more mobile sediment. We previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 95 publications
7
158
1
Order By: Relevance
“…The form drag caused by boulders increases with the number of boulders, resulting in lower shear stresses available at the bed for sediment entrainment (Bathurst, 1978;Lenzi et al, 2006;Yager et al, 2007Yager et al, , 2012. Hence, the presence of boulders decreases the sediment transport capacity (Yager et al, 2007(Yager et al, , 2012; Ghilardi and Schleiss, 2012). The effect of boulders on flow conditions (i.e., bed shear stress and bed resistance equations) and thus on sediment transport capacity can be accounted for via several morphological parameters, such as their protrusion, their cross section, the bed surface area occupied by them, the distance between boulders and a drag coefficient (Bathurst, 1978;Canovaro et al, 2007;Yager et al, 2007;Pagliara et al, 2008;Yager et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The form drag caused by boulders increases with the number of boulders, resulting in lower shear stresses available at the bed for sediment entrainment (Bathurst, 1978;Lenzi et al, 2006;Yager et al, 2007Yager et al, , 2012. Hence, the presence of boulders decreases the sediment transport capacity (Yager et al, 2007(Yager et al, , 2012; Ghilardi and Schleiss, 2012). The effect of boulders on flow conditions (i.e., bed shear stress and bed resistance equations) and thus on sediment transport capacity can be accounted for via several morphological parameters, such as their protrusion, their cross section, the bed surface area occupied by them, the distance between boulders and a drag coefficient (Bathurst, 1978;Canovaro et al, 2007;Yager et al, 2007;Pagliara et al, 2008;Yager et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Boulders that act as macro-roughness elements endure a significant part of the total stress and disrupt the flow by altering the channel roughness (Wohl, 2000;Yager et al, 2007;David et al, 2011). The form drag caused by boulders increases with the number of boulders, resulting in lower shear stresses available at the bed for sediment entrainment (Bathurst, 1978;Lenzi et al, 2006;Yager et al, 2007Yager et al, , 2012. Hence, the presence of boulders decreases the sediment transport capacity (Yager et al, 2007(Yager et al, , 2012; Ghilardi and Schleiss, 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although not a state variable, form drag is physically justifiable because larger clasts that protrude higher into the flow (e.g., stable boulders) tend to account for a disproportionate amount of the total stress through drag, turbulence generation and pressure gradients. Form drag corrections have been incorporated into many transport models to enable reasonable transport rates to be calculated using τ * c values typical of systems without form drag (e.g., Rickenmann and Recking, 2011;David et al, 2011;Yager et al, 2012a). Conversely, another common approach (and that taken here) is simply to use higher τ * c (e.g., Bunte et al, 2013;Lenzi et al, 2006), treating τ * c as a physically meaningful fitting parameter to predict transport.…”
Section: Form Drag Vs Parsimonymentioning
confidence: 99%
“…bends and irregular channel width), may be summarised as macro-roughness, which reduces the energy available for the transport of sediment. If macro-roughness is not accounted for in steep channels, bedload transport capacity may be greatly overestimated (Rickenmann, 2001Yager et al, 2007;Badoux and Rickenmann, 2008;Chiari and Rickenmann, 2011;Nitsche et al, 2011Nitsche et al, , 2012Yager et al, 2012). To correct for macroroughness, Nitsche et al (2011) suggested the use of a reduced energy slope, which represents a fraction of the real gradient, and which is based on a flow-resistance partitioning approach of Rickenmann and Recking (2011) and Nitsche et al (2011).…”
Section: Flow Resistancementioning
confidence: 99%